Exploring Collaborative Learning in Multimodal Writing: A Study on Student Experiences Using Canva - Rosmayanti, Vivit (Universitas Muhammadiyah Mataram, 2025)
Technology integration in education has become increasingly important, particularly in enhancing collaborative learning and multimodal writing. Platforms like Canva, which allow students to combine text with visual elements, are seen as valuable tools for fostering creativity and improving communication in collaborative projects. However, there is limited research on student experiences using such platforms in collaborative writing tasks, especially in EFL writing classroom. This study aims to explore students' experiences and perceptions of collaborative learning through multimodal writing using Canva, focusing on its impact on writing quality and digital literacy. A qualitative case study was conducted with 36 English Language Education program undergraduate students. Data were collected through semi-structured interviews and reflective journals. The findings reveal that Canva facilitated effective collaboration, improved writing quality, and enhanced creativity by allowing students to integrate graphic elements into their compositions. However, challenges such as technical issues, limited digital skills, and communication barriers were also identified. Despite these obstacles, students employed strategies like peer support, regular check-ins, and using alternative communication platforms to overcome difficulties. The study highlights the importance of providing digital literacy training and ensuring access to technology in educational settings. These findings suggest that platforms like Canva can significantly improve collaborative learning and digital literacy, offering valuable insights for educators seeking to integrate technology into their teaching practices.